Examination of AI-2 quorum sensing system Prevotella bryantii and Prevotella ruminicola-like strain by using bioluminiscence assay - Gorenc, Gregor (Acta agriculturae Slovenica, 2007)
Rumen is an example of a complex microbial ecosystem where extensive intraspecies as well as interspecies cell-cell cross-communication is expected, but little is known about. Four ruminal Prevotella strains, Prevotella bryantii B14, TC1-1 and TF1-3, and P. ruminicola-like strain 223/M2/7A were examined for the presence of AI-2 tzpe quorum sensing systems. Vibrio harveyi BB170 autoinducer bioassay was used in order to detect the production of AI-2 autoinducer in examined strains. Optimization of autoinducer bioassay was made to test the influence of sampling time and the substrate used in chemically defined medium CD on reporter strain luminescence signal. We discovered that AI-2 tzpe qurum sensing system is present in P. ruminicola-like strain 223/M2/7A, which induced more than 74% of reporter strain bioluminescence, regardless of the presence of glucose in chemically defined medium CD. Such induction of bioluminescence was not observed in P. bryantii strains, however.
Keywords: bakterije; mikrobi; mikrobiologija; prežvekovalci; vamp